Antispermatozoal antibodies : physiology, diagnosis and prognosis - Windt, Marie-Lena (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Med. Pharmacology)) -- University of Stellenbosch, 1989.